Association of Testosterone Replacement Therapy and the Incidence of a Composite of Postoperative In-Hospital Mortality and Cardiovascular Events in Men Undergoing Cardiac Surgery. (April 2020) - Argalious, Maged Y.; Steib, John; Daskalakis, Nikolas; Mao, Guangmei; Li, Minwei; Armanyous, Sherif; Roselli, Eric
Abstract : BACKGROUND: Data on testosterone replacement therapy and cardiovascular outcomes are conflicting, with the Food and Drug Administration requiring prescription testosterone preparations to indicate a possible increased cardiovascular risk. Whether patients on testosterone replacement therapy undergoing cardiac surgery have an increased risk of postoperative in-hospital mortality and cardiovascular events remains unknown. We therefore sought to identify the impact of testosterone replacement on the incidence of a composite of postoperative in-hospital mortality and cardiovascular events in men undergoing cardiac surgery. METHODS: After institutional review board approval, data from male American Society of Anesthesiologists III/IV patients ≥40 years of age who underwent cardiac surgery between May 2005 and March 2017 at the Cleveland Clinic (Cleveland, OH) main campus were included. The primary exposure was preoperative testosterone use. The primary outcome was a collapsed composite of postoperative in-hospital mortality and cardiovascular events, including myocardial infarction, stroke, and pulmonary embolism. The secondary outcome was a collapsed composite of minor cardiovascular events, including postoperative rhythm disturbance requiring permanent device, atrial fibrillation, and deep venous thrombosis. We compared patients who received testosterone and those who did not, using propensity score matching within surgical procedure matches. Moreover, as a sensitivity analysis, we used a multivariable logistic regression model to assess the association between testosterone replacement therapy and major or minor cardiovascular events adjusted for potential baseline and intraoperative confounders by including all eligible patients. RESULTS: Among 20, 604 patients who met inclusion and exclusion criteria, 301 patients who used testosterone routinely within 1 month before the surgery were matched to 1505 of 20, 303 patients who did not use testosterone. Among the matched cohort, 8 (2.7%) patients in the testosterone group and 45 (3.0%) in the nontestosterone group had ≥1 major cardiovascular adverse event after surgery. The adjusted odds ratio was 0.89 (95% CI, 0.41–1.90; P = .756), comparing testosterone to nontestosterone patients. As for the secondary outcomes, 89 (30%) patients in the testosterone group and 525 (35%) patients in the nontestosterone group had ≥1 minor cardiovascular event. The odds of minor events were not significantly different, with an odds ratio of 0.78 (95% CI, 0.60–1.02; P = .074) comparing testosterone to nontestosterone patients. CONCLUSIONS: Preoperative testosterone is not associated with a statistically significant increased incidence of a composite of postoperative in-hospital mortality and cardiovascular events after cardiac surgery.